Colloidal Metal Nanocrystals with Metastable Crystal Structures. (2nd February 2021) - Janssen, Annemieke; Nguyen, Quynh N.; Xia, Younan
Abstract: In addition to the conventional knobs such as composition, size, shape, and defect structure, the crystal structure (or phase) of metal nanocrystals offers a new avenue for engineering their properties. Various strategies have recently been developed for the fabrication of colloidal metal nanocrystals in metastable phases different from their bulk counterparts. With a focus on noble metals, we begin with a brief introduction to their atomic packing, followed by a discussion about five major synthetic approaches to their colloidal nanocrystals in unconventional phases. We then highlight the success of synthesis in terms of mechanistic insights and experimental controls, as well as the enhanced catalytic properties. We end this Minireview with perspectives on the remaining issues and future opportunities. Abstract : There is a strong interest in developing metal nanocrystals with well‐controlled shapes while featuring metastable crystal structures. The unconventional crystal phases not only enrich the diversity and functionality of nanomaterials but also enhance their catalytic properties.